FliA regulates the antibacterial activity of plantaricin BM-1 against Escherichia coli K-12 through the LuxS/AI-2 quorum-sensing-mediated biofilm formation - Wang, Shichun; Song, Xiaodong; Zheng, Xuan; Cheng, Congyang; Jin, Junhua; Xie, Yuanhong; Zhang, Hongxing (Frontiers in Microbiology, 2025)
IntroductionPlantaricin BM-1 is a class IIa bacteriocin active against Escherichia coli. However, the mode of action of class IIa bacteriocins against gram-negative bacteria remains unclear. In this study, the regulatory role of sigma factor FliA (σ28) in the antibacterial mechanism of plantaricin BM-1 against E. coli K-12 BW25113 is evaluated.MethodsThe fliA-complemented strain of E. coli JW1907, namely E. coli ReJW1907, was constructed through λ-Red homologous recombination. The effects of plantaricin BM-1 on E. coli growth, cell morphology, and membrane integrity were investigated using growth curves, electron microscopy, and flow cytometry. The biofilm formation ability of E. coli was evaluated using crystal violet staining and confocal laser scanning microscopy. Transcriptomic analysis was performed to screen for differentially expressed genes (DEGs).Results and discussionThe inhibition rate (I%) of plantaricin BM-1 (3.75 mg/mL) against E. coli JW1907 (89.22 ± 1.13%) at the 8th h of culture was significantly higher than that of E. coli BW25113 (70.36 ± 6.30%) and ReJW1907 (74.75 ± 4.99%). The biofilm biomass produced by E. coli BW25113 (OD595nm = 0.343 ± 0.056) was significantly reduced to 0.227 ± 0.04 after fliA deletion, and was recovered to its original level (0.358 ± 0.027) after fliA complement. A total of 205 DEGs were identified between E. coli BW25113 and JW1907. Among these, four DEGs (fliZ,wza, lsrR, and pgaA) were enriched in the biofilm formation pathway. Further analysis revealed eight up-regulated DEGs (lsrKRBDCAFG), which were significantly enriched in the LuxS/AI-2 quorum sensing (QS) system. After the deletion of any gene from lsrKRBDCAFG, the I% of plantaricin BM-1 against E. coli BW25113 (70.77 ± 7.01%) was significantly increased to 80.68–90.06%, with its biofilm production (0.254 ± 0.014) reduced to 0.135–0.188. In conclusion, FliA modulates biofilm formation through the LuxS/AI-2 QS system, thereby regulating the antibacterial activity of plantaricin BM-1. Overall, these findings improve our understanding of the bacteriostatic mechanism of class IIa bacteriocins against gram-negative bacteria.